(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Hydrogels are polymeric materials with exceptional water absorption properties, capable of retaining significant amounts of water and gradually releasing it into the soil. This unique characteristic makes hydrogels highly beneficial for managing field water supply, especially in regions experiencing water scarcity and unpredictable rainfall. By integrating hydrogels into the soil, it is possible to enhance water retention, reduce the frequency of irrigation, and promote healthier plant growth.